Uso de aditivos na redução do escurecimento de conservas de cebola branca e sua estabilidade - Campara, Beatris (2021)
Canned onions produced on an industrial scale undergo color changes and precipitate formation in the syrup, which influences negatively consumer acceptance. Among the strategies to inhibit these changes, it is possible to add chemical ingredients or additives with different technological functions in the covering syrup formulation (brine). Therefore, this study sought to evaluate the influence of the chemical additives potassium sorbate, sodium benzoate, and sodium metabisulfite used together in the formulation of the covering syrup for canned white onion. In addition to these additives, the addition of citric acid to the syrup formulation was also tested. In the first stage of the study, a base brine was used for all tests. It had vinegar, water, sodium chloride, and crystal sugar to investigate the physical chemical parameters pH, total acidity, sodium content, soluble solids, and vacuum. The onion preserves were evaluated at 20 and 240 days of storage. The formulations containing the chemical additives potassium sorbate, sodium benzoate, and sodium metabisulfite did not show any formation of precipitates ascribed to the presence of fungi. However, there was a browning of the brine and onions during the storage period, indicating that the concomitant use of the three additives was not appropriate. The formulations without the addition of sodium metabisulfite showed rapid browning of the onion bulbs and the syrup during storage, indicating the relevance of the presence of this additive in the formulation. The addition of citric acid (0.50 mg L-1) kept the pH of the brine lower, being effective in preventing the syrup darkening, the formation of stains, and precipitates. In the second stage of the study, we sought to statistically evaluate the effects of different dosages of citric acid and potassium sorbate. For that, tests were carried out with 9 different formulations, being evaluated along the storage time (0, 45, 90, and 145 days) the parameters pH, acidity, color, phenolic compounds, soluble solids, and fungus count. In the analysis of the principal components (CP), tests with different dosages of potassium sorbate and citric acid showed that the variables pH, acidity, ∆E*, and phenolic compounds were correlated with each other, composing the CP1, while the variables soluble solids and fungus count made up CP2. In the multivariate analysis of variance, a statistically significant difference (p < 0.05) was observed between the means for storage time and formulation. By Tukey's test, a significant difference is suggested mainly between the storage times evaluated and some formulations for pH, acidity, and soluble solids variables. The formulations with higher levels of citric acid (1 mg L-1) combined with the addition of sodium metabisulfite and potassium sorbate showed the best results to keep color and to prevent the appearance of precipitates.